KADAR PROTEIN, KADAR LEMAK DAN ORGANOLEPTIK TELUR ASIN ASAP BERBAHAN BAKAR SABUT KELAPA - Deni Novia; Indri Juliyarsi; Ganda Fuadi (State Islamic University of Sultan Syarif Kasim Riau, 2012)
This research aims to determine the effect different smoking and storaging time to protein content, fat content andorganoleptic value smoked salted eggs. This study used duck eggs as many as 240 eggs, powdered brick 3600 grams, 2400grams of ash, 1200 grams salt and 60 kg of coconut husk. The method used in this study was the experimental method usinga randomized block design with a 4x3 factorial with two groups as replicates. As the first factor (A) was different smoking A1= 8 hours, A2 = 10 hour, A3 = 12 hours and A4 = 14 hours, whereas the second factor (B) was storaging time : B1 = 23days, B2 = 30 days and B3 = 37 days. Variables measured were protein content, fat content, and organoleptic values (colour,flavor, aroma, texture) of smoked salted eggs. The results of this study different smoking and storaging time was nointeraction to all variables smoked salted eggs. It did not affect the flavor and aroma, but the longer smoking decreasedprotein content and colors but increased fat content. The longer it was stored the smoke salted eggs, increased fat content anddecreased texture. Based on the results of this study concluded that 8 hour smoking was the best treatment in themanufacture of smoked salted eggs with protein content 48,99%, fat content 45,82%, color 3,35 (ordinary), flavor 3,49 (like),aroma 2,73 (ordinary) dan texture 3,16 (ordinary)